Evaluating a streamlined clinical tool and educational outreach intervention for health care workers in Malawi: the PALM PLUS case study - Martiniuk Alexandra; Fairall Lara; Bateman Eric; Joshua Martias; Thompson Sandy; Burciul Barry; Kathyola Damson; Banda Hastings; Sodhi Sumeet; Cornick Ruth; Faris Gill; Draper Beverley; et al. (BMC, 2011)
Abstract Background Nearly 3 million people in resource-poor countries receive antiretrovirals for the treatment of HIV/AIDS, yet millions more require treatment. Key barriers to treatment scale up are shortages of trained health care workers, and challenges integrating HIV/AIDS care with primary care. The research PALM PLUS (Practical Approach to Lung Health and HIV/AIDS in Malawi) is an intervention designed to simplify and integrate existing Malawian national guidelines into a single, simple, user-friendly guideline for mid-level health care workers. Training utilizes a peer-to-peer educational outreach approach. Research is being undertaken to evaluate this intervention to generate evidence that will guide future decision-making for consideration of roll out in Malawi. The research consists of a cluster randomized trial in 30 public health centres in Zomba District that measures the effect of the intervention on staff satisfaction and retention, quality of patient care, and costs through quantitative, qualitative and health economics methods. Results and outcomes In the first phase of qualitative inquiry respondents from intervention sites demonstrated in-depth knowledge of PALM PLUS compared to those from control sites. Participants in intervention sites felt that the PALM PLUS tool empowered them to provide better health services to patients. Interim staff retention data shows that there were, on average, 3 to 4 staff departing from the control and intervention sites per month. Additional qualitative, quantitative and economic analyses are planned. The partnership Dignitas International and the Knowledge Translation Unit at the University of Cape Town Lung Institute have led the adaptation and development of the PALM PLUS intervention, using experience gained through the implementation of the South African precursor, PALSA PLUS. The Malawian partners, REACH Trust and the Research Unit at the Ministry of Health, have led the qualitative and economic evaluations. Dignitas and Ministry of Health have facilitated interaction with implementers and policy-makers. Challenges and successes This initiative is an example of South-South knowledge translation between South Africa and Malawi, mediated by a Canadian academic-NGO hybrid. Our success in developing and rolling out PALM PLUS in Malawi suggests that it is possible to adapt and implement this intervention for use in other resource-limited settings.